Perception of breath components by the tropical bont tick, Amblyomma variegatum Fabricius (Ixodidae): I. CO2-excited and CO2-inhibited receptors - Steullet, Pascal; Guerin, Patrick (My University, 1992)
Wall-pore olfactory sensilla located in the capsule of Haller's organ on the tarsus of Amblyomma variegatum ticks bear cells responding to vertebrate breath: one of these sensilla contains a CO2-excited receptor and a second sensillum has a CO2- inhibited receptor. Each of these antagonistic CO2-receptors, which display typical phasic-tonic responses, monitors a different CO2-concentration range. The CO2-inhibited receptor is very sensitive to small concentration changes between 0 and ca. 0.2%, but variations of 0.01% around ambient (ca. 0.04%) induce the strongest frequency modulation of this receptor. An increase of just 0.001–0.002% (10–20 ppm) above a zero CO2-level already inhibits this receptor. By contrast, the CO2-excited receptor is not so sensitive to small CO2 shifts around ambient, but best monitors changes in CO2 concentrations above 0.1%. This receptor is characterized by a steep dose-response curve and a fast inactivation even at high CO2-concentrations (>2%). In a wind-tunnel, Amblyomma variegatum is activated from the resting state and attracted by CO2 concentrations of 0.04 to ca. 1%, which corresponds to the sensitivity range of its CO2-receptors. The task of perceiving the whole concentration range to which this tick is attracted would thus appear to be divided between two receptors, one sensitive to small changes around ambient and the other sensitive to the higher concentrations normally encountered when approaching a vertebrate host.
Keywords: Tick; CO2-excited receptor; CO2-inhibited receptor; Haller's organ; Host finding